Anxiety and cognitive load affect upper limb motor control in Parkinson's disease during medication phases. Issue 1 (21st January 2021) - Nodehi, Zahra; Mehdizadeh, Hajar; Azad, Akram; Mehdizadeh, Maryam; Reyhanian, Elham; Saberi, Zakieh Sadat; Meimandi, Mahsa; Soltanzadeh, Akbar; Roohi‐Azizi, Mahtab; Vasaghi‐Gharamaleki, Behnoosh; Parnianpour, Mohamad; Khalaf, Kinda; et al.
Abstract: Anxiety is among the most debilitating nonmotor symptoms of Parkinson's disease (PD). This study aimed to determine how PD patients with low and high levels of anxiety (LA‐PD and HA‐PD, respectively) compare with age‐ and sex‐matched controls at the level of motor control of reach‐to‐grasp movements during single‐ and dual‐task conditions with varying complexity. Reach‐to‐grasp movement kinematics were assessed in 20 LA‐PD, 20 HA‐PD, and 20 sex‐ and age‐matched healthy controls under single‐ as well as easy and difficult dual‐task conditions. Assessment of PD patients was performed during both the on‐ and off‐drug phases. The results obtained during dual‐task conditions reveal deficits in both reach and grasp components for all three groups (e.g., decreased peak velocity and delayed maximum hand opening). However, these deficits were significantly greater in the PD groups, especially in the HA‐PD group. Although dopaminergic medication improved reach kinematics, it had no effect on grasp kinematics. The results of our study indicated that high levels of anxiety may enhance the inefficiency of upper limb motor control in PD patients, especially during high demanding cognitive conditions, and should, therefore, be considered in the assessment and planning of interventions for upper limb function in these patients. Abstract : Our study indicates that when Parkinson's disease (PD) patients are burdened by a high cognitive load, they demonstrate increased inefficiency in reach‐to‐grasp motor control integral to most daily life activities, an inefficiency, moreover, that is exacerbated by high levels of anxiety. These findings highlight the importance of design and incorporation of effective pharmacological/behavioral interventions for anxiety in PD patients. Our findings also suggest that the dual‐task assessment of upper limb motor control and function might be appropriate for investigating PD patients over time to document the progressive decline of upper limb motor control due to disease progression, or its improvement, resulting from neuroprotective interventions.